The brain takes shape : an early history - Martensen, Robert L. (Robert Lawrence) (Oxford University Press, 2004)
1. Bodies, Words, and Images. 2. Matter, Spirit, and the Heart. 3. The Human Mind and "Gland H": Cartesian Models of Mind, Brain, and Nerves. 4. When the Brain Came Out of the Skull. 5. Toward a New Physiology of Human Conduct. 6. Body of Witnesses. 7. The Transformation of Eve. 8. Mind Without Brain: John Locke, Thomas Syndenham, and the Constitutional Body of the British Enlightenment. 9. On the Persistence of the Cerebral Model and Its Alternatives: A Cultural Anthropology Perspective.
Keywords: Medicine -- Philosophy.; Human body (Philosophy); Medicine -- History -- 17th century.; Philosophy, Medical -- history; History, 17th Century; Philosophy, Medical; Médecine -- Philosophie.; Corps humain (Philosophie); Médecine -- Histoire -- 17e siècle.; MEDICAL -- Family & General Practice.; MEDICAL -- Osteopathy.; MEDICAL.; MEDICAL -- Holistic Medicine.; HEALTH & FITNESS -- Reference.; MEDICAL -- Essays.; MEDICAL -- Alternative Medicine.; HEALTH & FITNESS -- Holism.; Medicine; Medicine -- Philosophy; Lichaam en geest.; Hersenfuncties.; Filosofische aspecten.; Theologie.; Leib-Seele-Problem; Medizin; Philosophie; 1600-1699; Geschichte; Geschichte 1600-1700; History; Electronic books.